Beyond Strategy: Exploring Cultural Familiarity, Metacognition, and Learner Autonomy in Reading Comprehension: - Kunene, Mfanukhona Wonderboy; Nyika, Nicholus (ELE Reviews: English Language Education Reviews, 2025)
Literature on reading strategies ignores the critical role of cultural familiarity in the strategic selection and metacognition control of learners. This phenomenological study explores the rationale for implementing reading strategies and for metacognitive control among learners in culturally familiar and unfamiliar texts. The paper argues that cultural context shapes the reasons for using or abandoning a specific strategy, a process controlled by learners’ autonomy. The findings show that learners commonly use Global strategies to attain efficiency with known texts. However, they use Problem-Solving strategies when texts become culturally irrelevant, indicating a strong strategic bifurcation. The Reading Comprehension Pathway (RCP) Model embodies this strategic process and reconceptualises comprehension as a dynamic pathway under cultural control. The RCP Model provides a general framework for developing culturally responsive English Language Teaching (ELT) pedagogy.